Nas linhas da justiça: uma análise feminista sobre os acórdãos judiciais de violência contra as mulheres do Tribunal de Justiça de Minas Gerais (1998 - 2015) - Luciana Vieira Rubim Andrade (2017)
This dissertation analyses which factors influence the decisions made by state supreme court justices of the Brazilian State Supreme Court of Minas Gerais (TJMG), a state court of appeals, in cases of violence against women, seeking to unravel the reasons why such decisions frequently reinforce gender injustices. Based on an essentialist feminist approach, we shed light on the deadlocks that the Lei Maria da Penha (LMP) - a Brazilian federal law targeted to reduce domestic violence against women - continues to face for being fully enforced and guaranteeing women's human rights. The study is exploratory and takes court decisions as units of analysis, spanning from 1998 to 2015, and employ both qualitative and descriptive methods as well as interviews with state supreme justices from Minas Gerais. Our results show that while the number of cases of violence against women judged by the TJMG rose substantially after the LMP enactment and constitutionalization process, its use as legislative reference on court decisions are dropping. Additionally, justices' individual decisions are heterogeneous, and reinterpretations of the legislative rules are the main form of not exerting the LMP. Lastly, the questions of conditioned versus unconditioned representation and the exertion and enforcement of protective measures to the aggressors are still the major obstacles that must be overcome for the LMP to be effective.